Electrical energy generation from nanowire structures - Attab, Rasol R. (University of Thi-Qar Journal of Science, 2014)
This work numerically estimate the amount of electric voltage generation from Zing oxide, Barium titanium, Gallium nitride, Lead zirconate titanate (ZnO, BaTiO3, GaN and PZT) nanowire structure respectively and other hetro-structure or doped structure like (ZnMgO, GaAlN) having rectangular and circular cross sections with dimension of length and width (l , b) 600,50 nanometers. The amount of the generated voltage seem enough to power biosensor, nanosensor, or even biomedical device. The effect of nanowire length, width and temperature and the effect of applied force are studied, All theses parameters having profound effect on the amount of the maximum generated voltage